A case of spontaneous abortion related to ovarian endometriosis in a Golden Retriever dog - Demirel, M. A. (Iran J Vet Res, 2017)
This report describes a case of spontaneous abortion in a 4-year-old Golden Retriever dog with ovarian endometriosis. Clinical findings indicated that there was not any senstivity in the abdomen and the viability parameters were within the reference values. On vaginal examination, serosanguineous discharge was determined. Ultrasonographic examination revealed that no fetus was observed in cornu uteri and an hypoechoic cystic structure, measuring 3.2 × 3.4 cm was found behind the left kidney. Ovarian cyst was suspected, and then ovariohysterectomy was performed. On laparotomy, the presence of a cystic structure was confirmed in the left ovary similar to ultrasonographic findings. Cyst was smooth, flat, hemorrhagic and thick-walled structure. Histopathologic examination of the ovarian stroma revealed covered luteinizing cells and midline hemorrhagic cyst. However, the internal surface of the cyst wall was covered by an endometrial lining. Interestingly, the endometriotic tissue had a maximal penetration into the cyst wall. It was thought that the ovarian endometriosis caused a failure in the luteinizing hormone action which is responsible for luteal function and spontaneous abortion was observed in this case. Although ovarian endometriosis is quite usual in human, this case could be the first report to describe ovarian endometriosis in a dog, and thus it has been reported to cause spontaneous abortion.